Information and communication technology-based interventions for suicide prevention implemented in clinical settings: a scoping review protocol. Issue 1 (31st January 2022) - Shin, Hwayeon Danielle; Zaheer, Juveria; Rodak, Terri; Torous, John; Strudwick, Gillian
Abstract : Introduction: There is a surplus of information and communication technology (ICT)-based interventions for suicide prevention. However, it is unclear which of these ICT-based interventions for suicide prevention have been implemented in clinical settings. Furthermore, evidence shows that implementation strategies have often been mismatched to existing barriers. In response, the authors recognise the critical need for prospectively assessing the barriers and facilitators and then strategically developing implementation strategies. This review is part of a multiphase project to develop and test tailored implementation strategies for mobile app-based suicide prevention in clinical settings. The overall objective of this scoping review is to identify and characterise ICT-based interventions for all levels of suicide prevention in clinical settings. Additionally, this review will identify and characterise the barriers and facilitators to implementing these ICT-based interventions as well as reported measures and outcomes. The findings will directly inform the subsequent phase to maximise implementation and inform future efforts for implementing other types of ICT-based interventions related to suicide prevention in clinical settings. Methods and analysis: This review will adhere to the methods described by the Joanna Briggs Institute for conducting scoping reviews. The reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping review checklist. The following databases will be searched: Medline, PsycInfo, Embase, Cumulative Index to Nursing & Allied Health Literature (CINAHL), Web of Science and Library, Information Science & Technology Abstracts (LISTA). Two reviewers will independently screen the articles and extract data using a standardised data collection tool. Then, authors will characterise extracted data using frameworks, typology and taxonomies to address the proposed review questions. Ethics and dissemination: Ethics approval is not required for this scoping review. Authors will share the results in a peer-reviewed, open access publication and conference presentations. Furthermore, the findings will be shared with relevant health organisations through lay language summaries and informal presentations.